Northwest history. Mining. Discovery. 1931-04-05 (1931)
Savage finds new promise. - Reports gold, lead and silver on cleavinger group -- ignored for decades. - Promise is reported by M. L. Savage of Wallace, Idaho, in an area on the west side of Beaver creek, opposite the Clear Grit cabins, that has been passed up for decades by others seeking properties for development.